(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Buffalo semen collected from Murrah bull were cryopreserved and evaluated for different motility parameter, kinematics and plasma membrane integrity. Buffalo bulls were maintained uniform standard management and nutritional practices. Semen was collected regularly twice a week semen collection schedule from four (04) Murrah bull. Collected semen was immediately transported to laboratory and evaluated for different macroscopic parameter (color, volume and thickness). Fresh semen was then diluted with saline solution and evaluated for sperm concentration, motility, sperm kinematics and morphology. Semen samples that fill all the standard were selected for freezing and diluted with Tris-egg yolk citrate diluter. Diluted semen was equilibrated, cryopreserved and finally evaluated for post thaw sperm quality. Different motility parameter (total, progressive, static and slow motility) varied significantly (p<0.01) irrespective of different freezing stages. Significantly higher progressive sperm motility and viability of buffalo spermatozoa were observed at fresh semen whereas lower progressive sperm motility and viability was found at post thaw stage. Total and progressive motility reduced by 2.5 and 2.12% following equilibration, whereas following cryopreservation, total and progressive motility reduced by 35.7 and 28.51% and static motility increases accordingly (35.4%). Significantly higher plasma membrane integrity of sperm was observed at fresh semen followed by pre freeze and post thaw semen. Following freezing, integrity of plasma membrane reduces at the rate of 10.81% and 26.7% at pre freezing and post thaw stages. Significantly higher average path velocity (VAP), straight line velocity (VSL), curvilinear velocity (VCL), straightness (STR), amplitude of lateral head displacement (ALH) and beat cross frequency (BCF) were found for fresh semen followed by pre-freeze and post-thaw semen. Frozen buffalo semen with higher progressive motility and motion characteristics may be produced if motility losses can be reduced during freezing stage as this stage results higher motility losses. Asian Australas. J. Biosci. Biotechnol. 2022, 7(2), 75-81